Infrastructural Facilities Development in Krishi Vigyan Kendras inRajasthan-A Comparative Assessment (Indian Journal of Extension Education, 2010)
Agriculture is the main stay of India’s economy onwhich 70 percent of total population depends directly.Role of agricultural information in the production of food grains has been always critical, because farmer’s are always want of new information/ technical know how. In this regard Govt. of India and States Government launched several transfer of technology programmes through which new advances in agricultural could be conveyed to farmers effectively.